Stabilization of a Silaaldehyde by its η2 Coordination to Tungsten. (24th November 2015) - Fukuda, Tetsuya; Hashimoto, Hisako; Sakaki, Shigeyoshi; Tobita, Hiromi
Abstract: Treatment of pyridine‐stabilized silylene complexes [(η 5 ‐C5 Me4 R)(CO)2 (H)WSiH(py)(Tsi)] (R=Me, Et; py=pyridine; Tsi=C(SiMe3 )3 ) with an N‐heterocyclic carbene Me I i Pr (1, 3‐diisopropyl‐4, 5‐dimethylimidazol‐2‐ylidene) caused deprotonation to afford anionic silylene complexes [(η 5 ‐C5 Me4 R)(CO)2 WSiH(Tsi)][H Me I i Pr] (R=Me (1‐Me ); R=Et (1‐Et )). Subsequent oxidation of1‐Me and1‐Et with pyridine‐ N ‐oxide (1 equiv) gave anionic η 2 ‐silaaldehydetungsten complexes [(η 5 ‐C5 Me4 R)(CO)2 Wη 2 ‐OSiH(Tsi)][H Me I i Pr] (R=Me (2‐Me ); R=Et (2‐Et )). The formation of an unprecedented W‐Si‐O three‐membered ring was confirmed by X‐ray crystal structure analysis.